2020
DOI: 10.1177/2048004020957840
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 and soluble ST2 as complementary tools to cardiac MRI for sudden cardiac death risk stratification in heart failure: A review

Abstract: Heart failure (HF) is recognized as one of the leading causes of morbidity and mortality worldwide. Every year about 500,000 new cases of HF are diagnosed in the United States. The predominant etiology of death in HF patients include sudden cardiac death (SCD) and pump failure. Prediction of mode of death may help in devising management decisions. In patients with HF, the presence of myocardial fibrosis has been a known risk factor for SCD and thus it could be used as a criterion in risk stratification for SCD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 49 publications
0
8
0
1
Order By: Relevance
“…An important advantage of ST2 is that its value does not vary with age, sex, body mass index, renal function or heart failure history, as in the case of BNP, NT-proBNP or hs-troponin [ 41 ]. Several studies have demonstrated the prognostic utility of soluble ST2 in patients with acutely decompensated heart failure, high levels of sST2 being associated with an increased risk of heart failure complications, such as arrhythmia, pump failure or death, independent of other cardiac biomarkers [ 42 , 43 , 44 , 45 ]. Additionally, the prognostic value of sST2 in patients with mild-to-moderate heart failure with LV systolic dysfunction was investigated by Pascual-Figal et al Their results suggest that elevated sST2 values tend to predict the risk of sudden cardiac death in patients with heart failure and may also improve prognostic strategies in heart failure management [ 46 ].…”
Section: Biomarkers Of Myocyte Stress/stretchmentioning
confidence: 99%
“…An important advantage of ST2 is that its value does not vary with age, sex, body mass index, renal function or heart failure history, as in the case of BNP, NT-proBNP or hs-troponin [ 41 ]. Several studies have demonstrated the prognostic utility of soluble ST2 in patients with acutely decompensated heart failure, high levels of sST2 being associated with an increased risk of heart failure complications, such as arrhythmia, pump failure or death, independent of other cardiac biomarkers [ 42 , 43 , 44 , 45 ]. Additionally, the prognostic value of sST2 in patients with mild-to-moderate heart failure with LV systolic dysfunction was investigated by Pascual-Figal et al Their results suggest that elevated sST2 values tend to predict the risk of sudden cardiac death in patients with heart failure and may also improve prognostic strategies in heart failure management [ 46 ].…”
Section: Biomarkers Of Myocyte Stress/stretchmentioning
confidence: 99%
“…Previous studies have identified higher circulating galectin-3 levels predicting the onset of HFpEF [ 32 , 33 ]. In addition to LGE-MRI, galectin-3 seems to play an important role in the sudden death risk stratification of heart failure patients [ 34 ]. Our study confirms the predictive value of galectin-3 in the diagnosis of cardiac fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the impaired cardiac contractility, fibrosis also interferes with the normal electrical signals within the heart, which predisposes to arrhythmias and fibrillation [ 118 , 119 ]. Overall, fibrosis has thus been proposed as a risk factor in HF as it predisposes to ventricular systolic and diastolic dysfunction [ 120 , 121 , 122 ], cardiomyocyte hypertrophy [ 122 , 123 , 124 ] and sudden cardiac death [ 125 , 126 ], thereby increasing mortality [ 127 , 128 ].…”
Section: Pathophysiology Of Crsmentioning
confidence: 99%